2005
DOI: 10.1007/s10531-004-9786-z
|View full text |Cite
|
Sign up to set email alerts
|

Remotely sensed landscape heterogeneity as a rapid tool for assessing local biodiversity value in a highly modified New Zealand landscape

Abstract: Abstract. The widespread conversion of natural habitats to agricultural land has created a need to integrate intensively managed landscapes into conservation management priorities. However, there are no clearly defined methods for assessing the conservation value of managed landscapes at the local scale. We used remotely sensed landscape heterogeneity as a rapid practical tool for the assessment of local biodiversity value within a predominantly agricultural landscape in Canterbury, New Zealand. Bird diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 72 publications
0
10
0
2
Order By: Relevance
“…Most of these characteristics represent conditions of environmental variability on a local scale. Comparable results have been reported for regional scales [24,36], showing a variable relative importance depending upon the scale [18]. According to Kolasa & Rollo [63], heterogeneity may be mostly explained by three components: (i) the environmental variability or range in which the different environmental conditions of the site are variable (number of habitat types); (ii) the spatial configuration of the different habitats of the site; and (iii) by the historical variation over time.…”
Section: Spatial Predictionmentioning
confidence: 91%
See 3 more Smart Citations
“…Most of these characteristics represent conditions of environmental variability on a local scale. Comparable results have been reported for regional scales [24,36], showing a variable relative importance depending upon the scale [18]. According to Kolasa & Rollo [63], heterogeneity may be mostly explained by three components: (i) the environmental variability or range in which the different environmental conditions of the site are variable (number of habitat types); (ii) the spatial configuration of the different habitats of the site; and (iii) by the historical variation over time.…”
Section: Spatial Predictionmentioning
confidence: 91%
“…The results of this research did not allow us to confirm the spectral variation hypothesis on a local scale, even though Oldeland et al [56] suggested that the use of hyperspectral information should improve monitoring of species diversity. In this light, recent studies [43,44] have proven that the hyperspectral information from airborne sensors can significantly enhance the predictive power of models not only because of the spectral information but also because of the improvement provided by the spatial resolution [24,26,41,58,59]. Another relevant source of information could be an analysis of seasonal and annual variability that can provide an additional element in estimating biodiversity [24], particularly in deciduous forests like Monte Oscuro.…”
Section: Ecological Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The area was chosen for method application since suitable data for the approach were available and since the location included protected areas (PAs) and non-protected areas. We consider the presence of PAs within the borders of the study area useful for the discussion of results, since today it is well recognized that successful biodiversity conservation can be achieved more effectively if the management plans of the PAs are integrated with those of the surrounding landscape matrix (Eigenbrod et al, 2008;Foody, 2008;Turner et al, 2008;Ewers et al, 2005;Vandewoestijne et al, 2005;Fahrig, 2003;Hannah et al, 2002).…”
Section: The Study Areamentioning
confidence: 99%